The quiescent centre of the root apical meristem: conceptual developments from Clowes to modern times. (23rd June 2021) - Dubrovsky, Joseph G; Ivanov, Victor B
Abstract : Here we discuss conceptual developments, from the organization of the quiescent centre to understanding its functions in root apical meristem maintenance and activity, and from model to crop species. Abstract: In this review we discuss the concepts of the quiescent centre (QC) of the root apical meristem (RAM) and their change over time, from their formulation by F.A.L. Clowes to the present. This review is dedicated to the 100th anniversary of the birth of Clowes, and we present his short biography and a full bibliography of Clowes' work. Over time, the concept of the QC proved to be useful for the understanding of RAM organization and behaviour. We focus specifically on conceptual developments, from the organization of the QC to understanding its functions in RAM maintenance and activity, ranging from a model species, Arabidopsis thaliana, to crops. Concepts of initial cells, stem cells, and heterogeneity of the QC cells in the context of functional and structural stem cells are considered. We review the role of the QC in the context of cell flux in the RAM and the nature of quiescence of the QC cells. We discuss the origin of the QC and fluctuation of its size in ontogenesis and why the QC cells are more resistant to stress. Contemporary concepts of the organizer and stem cell niche are also considered. We also propose how the stem cell niche in the RAM can be defined in roots of a non-model species.